HUBUNGAN KINERJA OTAK DENGAN SPIRITUALITAS MANUSIA DIUKUR DENGAN MENGGUNAKAN INDONESIA SPIRITUAL HEALTH ASSESSMENT PADA PEMIMPIN AGAMA DI KOTA TOMOHON - Dadana, Jendy Cliff (eBiomedik, 2013)
Abstract: Neuroscience is a science about the nervous system or neurons. The development of neuroscience has touched the spiritual dimension. There are four things if being combined will result in spirituality, as follows: meaning of life, positive emotions, spiritual experiences, and rituals. By using SPECT, Daniel Amen divided the brain into five major systems namely prefrontal cortex, limbic system, basal ganglia, gyrus cingulatus, and temporal lobes. All these five systems have correlation with spirituality. There are tools that can measure and describe the correlation of spirituality with brain inter alia Indonesia Spiritual Health Assessment..(ISHA).)This study aimed to determine the correlation between the brain performance with the spirituality in religious leaders in Tomohon city. This was a descriptive study with analytical survey method. Samples were 51 GMIM priests. Data of this study were analyzed by using the Spearman correlation test. The results showed that the average value of the brain, especially the limbic system, was 5.80 (good), where as the spirituality, especially ritual, was 155.50 (very good). The Spearman Correlation test showed a P-value = 0,013, which means the correlation between the two variables was significant. Conclusion: There was a significant correlation between the brain performance and the human spirituality measured by using ISHA in religious leaders at Tomohon City. Keywords: brain, ISHA, religious leaders, spirituality     Abstrak: Neurosains adalah ilmu yang mempelajari tentang sel saraf atau neuron. Perkembangan neurosains telah menyentuh dimensi spiritual. Terdapat empat hal yang bila digabungkan akan menghasilkan spiritualitas yaitu makna hidup, emosi positif, pengalaman spiritual, dan ritual. Melalui jasa SPECT, Daniel Amen membagi otak dalam lima sistem utama yaitu: korteks prefrontalis, sistem limbik dalam, ganglia basalis, girus singulatus, dan lobus temporalis. Kelima sistem ini memiliki hubungan dengan spiritualitas. Alat yang dapat mengukur spiritualitas serta menggambarkan hubungannya dengan otak, antara lain ialah Indonesian Spiritual Health Assessment (ISHA). Penelitian ini bertujuan untuk mengetahui hubungan kinerja otak dan spiritualitas pada pemimpin agama di kota Tomohon. Penelitian ini bersifat deskriptif dengan metode survei analitik. Sampel penelitian ialah pendeta-pendeta GMIM dengan jumlah 51 orang. Data penelitian dianalisis menggunakan uji korelasi Spearman. Nilai rata-rata otak khususnya sistem limbik yaitu 5,80 (baik), sedangkan spiritualitas khususnya ritual yaitu 155,50 (sangat baik). Hasil uji korelasi Spearman menunjukkan nilai P = 0,013 yang berarti hubungan kedua variabel bermakna. Simpulan: Terdapat hubungan bermakna antara kinerja otak dan spiritualitas manusia diukur dengan menggunakan ISHA pada pemimpin agama di kota Tomohon. Kata kunci: ISHA,otak, pemimpin agama, spiritualitas.